Use of unmanned aerial vehicle (UAV) in the identification of surface pathology in asphalt pavement - Parente, Dénis Cardoso; Felix, Natália Carvalho; Picanço, Aurélio Pessoa (Revista ALCONPAT, 2017)
The present research had the purpose of developing an alternative and new procedure to identify the surface pathological manifestations in asphaltic pavement of a stretch of highway TO-050, in Palmas - TO. An unmanned aerial vehicle (UAV), flight plan and image processing software, orthophotos and Digital Surface Model (MDS) of the study area were used as tool. By means of the visual interpretation of the generated products it was possible to identify the pathological manifestations in its variety, comparing data obtained through the images with in loco inspection data. Even though it presents a high potential for recognition of compromised areas, it is important to highlight that the instability of the aircraft interferes considerably with the quality of the images generated.